2008
DOI: 10.1063/1.2905291
|View full text |Cite
|
Sign up to set email alerts
|

Strong work-hardening effect in a multiphase ZrCuAlNiO alloy

Abstract: A bulk as-cast ZrCuAlNiO alloy consisting of Zr2Cu, B2-type ZrCu, and a small quantity of ZrCu martensite phase was prepared by copper mold casting. The multiphase alloy exhibits a remarkable work-hardening effect (Δσy=1196MPa, ΔE=5.6GPa, and Δεe=2.11%) in the cycle loading-unloading compression test and possesses the high work-hardening capacity (Hc) of 1.66 and 1.58 at strain rates of 1×10−4 and 1×10−3s−1, respectively, under continuous deformation. The strong work-hardening effect of the alloy results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…It is important to note here that the B2 CuZr phase can only be obtained from the glassy state by proper adjustment of the cooling rate. Annealing treatments of glassy alloys lead to the formation of metastable phases or the precipitation of the equilibrium phases, depending on the composition [20].To the best of the authors' knowledge only the formation of martensite in Cu-Zr-based partially glassy alloys upon quenching has been reported so far [19,[21][22][23][24]. This is due to the stresses in the material that occur during the solidification process that usually trigger martensite formation.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…It is important to note here that the B2 CuZr phase can only be obtained from the glassy state by proper adjustment of the cooling rate. Annealing treatments of glassy alloys lead to the formation of metastable phases or the precipitation of the equilibrium phases, depending on the composition [20].To the best of the authors' knowledge only the formation of martensite in Cu-Zr-based partially glassy alloys upon quenching has been reported so far [19,[21][22][23][24]. This is due to the stresses in the material that occur during the solidification process that usually trigger martensite formation.…”
mentioning
confidence: 90%
“…To the best of the authors' knowledge only the formation of martensite in Cu-Zr-based partially glassy alloys upon quenching has been reported so far [19,[21][22][23][24]. This is due to the stresses in the material that occur during the solidification process that usually trigger martensite formation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been demonstrated that oxygen impurity at a level of 0.3 at% dramatically reduces the glass forming ability (GFA). 21,22) Therefore, it can be deduced that the presence of 0.56 at% oxygen in the ZrCuAlNiO alloy deteriorates the GFA and triggers the formation of the crystalline phases. In addition, the oxygen addition may stabilize the ZrCu (B2) crystalline phase.…”
Section: Methodsmentioning
confidence: 99%
“…12,13) The ZrCu martensites and ZrCu (B2) phases could be used as reinforcement in the Zr-Cu(Ni) based alloys to improve the strength and toughness of the materials. [15][16][17][18][19][20][21] In addition, the Zr-Cu(Ni) system exhibits particular promise for developing precipitation-strengthened multiphase alloys. However, a problem is the incomplete knowledge of the stability of various phases in Zr-Cu(Ni) system alloy at high temperatures.…”
Section: Introductionmentioning
confidence: 99%